Hack proofing XML - 'Ken'@ftu. (Rockland, Mass. : Syngress Media ; London : International Thomson, 2002)
The only way to stop a hacker is to think like one! The World Wide Web Consortium's Extensible Markup Language (XML) is quickly becoming the new standard for data formatting and Internet development. XML is expected to be as important to the future of the Web as HTML has been to the foundation of the Web, and has proven itself to be the most common tool for all data manipulation and data transmission. Hack Proofing XML provides readers with hands-on instruction for how to secure the Web transmission and access of their XML data. This book will also introduce database administrators, web developers and web masters to ways they can use XML to secure other applications and processes. The first book to incorporate standards from both the Security Services Markup Language (S2ML) and the Organization for the Advancement of Structured Information Standards (OASIS) in one comprehensive book Covers the four primary security objectives: Confidentiality, Integrity, Authentication and Non-repudiation Not only shows readers how to secure their XML data, but describes how to provide enhanced security for a broader range of applications and processes.
Includes index.
Keywords: XML (Document markup language); Computer security; Electronic books